(untitled) (Third Sector Social Economic Review, 2019)
Experience is the result of the interactions of the customer with a given product or brand. Customers who have had happy and emotionally appealing experiences tend to buy the same products again. The purchasing decision is also closely related to customers’ emotions. Therefore, revealing how experience and subjective well-being relates to customer satisfaction can provide valuable insights for businesses. This study aims to analyze the effects of clients’ experience and subjective well-being on customer satisfaction and to find out whether subjective well-being functions as a mediator in the relationship between customer experience and satisfaction. It is widely believed that positive experiences that customers may have when they eat or drink out could increase their level of happiness. Developing marketing strategies that could increase the happiness of their target audiences is, therefore, an issue that deserves careful consideration. The tests which carried out based on the structural equation modeling revealed a significant positive effect of the level of relational experience on the level of personal happiness and satisfaction